Pengaruh Modal Sosial Terhadap Pendapatan Musisi Kafe di Yogyakarta - Prabowo, Yulius Andar (Cerdika: Jurnal Ilmiah Indonesia, 2025)
This study aims to examine the influence of social capital on the income of café musicians in Yogyakarta, a city with a vibrant music ecosystem yet stagnant musician welfare. Using a qualitative approach, data were collected through in-depth interviews with three key informants: a café musician, a café manager, and an individual who serves as both musician and manager. The findings indicate that social capital—such as professional networks, trust, and reputation—plays a significant role in providing work opportunities. However, social capital alone is insufficient to improve income optimally without being supported by self-management, performance quality, and negotiation skills. This research highlights the importance of a holistic approach to evaluating musicians’ well-being and the need for collaboration between musicians and café managers. It also emphasizes that musicians’ income results from the interaction of social, cultural, and symbolic capital. Therefore, strengthening social networks must be accompanied by strategic economic planning and professional self-awareness to build a fairer and more sustainable café music ecosystem.